(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
BACKGROUND: Attitude of healthcare workers i.e., Specialist doctors, Resident doctors and Interns towards psychiatry is important in shaping the attitude of medical students, as well as the common public that they interact with on a day-to-day basis, towards psychiatry. The data available currently in this context is limited. AIMS: The aim of the study is to assess and compare the attitude of healthcare workers (Specialists, Residents and Interns) towards psychiatry in a tertiary care hospital. METHODS: 150 healthcare workers including 44 interns, 70 Residents and 36 specialists of Medical/Surgical/Non-clinical field fulfilling the inclusion criteria were evaluated by Attitude towards Psychiatry scale (ATP-30). Independent t-test and other tests were used for statistical analysis. RESULTS: Mean ATP score came out to be 99.6. Female gender (101.01), having a family member with psychiatric illness (102.81) & medical specialty (100.28) were associated with higher ATP scores. 80% of the participants reported that psychiatric illnesses are as important as physical illnesses and 73% felt that psychiatric interventions in recent times are effective. Average ATP score of interns (101.90) was more than that of residents (98.98) and specialist doctors (97.97). CONCLUSIONS: With changing times, the view towards psychiatric illnesses and psychiatry as a whole has been gradually improving. The COVID pandemic has shown us importance of mental health. A positive attitude towards psychiatry among healthcare workers will aid in decreasing the stigma towards psychiatry among general population.